Akuntansi dan Laba Rugi dalam Sebuah Pemaknaan: Studi Fenomenologi pada Pedagang Kaki Lima - Arwanda, Febry; Aditya, Dimas; Laire, Wahyu Laksana Caesar; Ginting, Rafles (Eksos, 2023)
This study aims to reveal the meaning of profit and loss for street vendors in the auditorium area of Tanjungpura University. This study uses a qualitative approach with a phenomenological method. Data were collected through in-depth interviews with ten street vendors who were purposively selected. The results of the study show that the meaning of profit and loss for street vendors is not only determined by the amount of income and expenditure, but also by other factors such as customer satisfaction, social relations, health, security, and self-confidence. Street vendors have different ways of calculating and managing profit and loss, as well as strategies to overcome the risks and challenges they face. This study contributes to understanding the microeconomic phenomenon from the subjective perspective of informal business actors.